Scientific rationality, adoption and perceived effectiveness of traditional agricultural practices of cassava (Manihot esculenta Crantz.) in Kolli Hills, India - Venkatesan, Purushothaman; Sundaramari, Mariappan (JOURNAL OF ROOT CROPS, 2015)
The tribes of the Kolli hills of Namakkal district in Tamil Nadu possessed rich tradition, heritage and experience in agriculture. Hence, an intensive study was found essential to identify, document, and analyze the Indigenous Tribal Agricultural Practices (ITAPs) of Kolli hills in Tamil Nadu. In this context a study was undertaken for collecting, classifying, documenting, analyzing the rationality, and studying the adoption of the selected ITAPs in tapioca. About 17 ITAPs on tapioca cultivation, in different clusters of villages of Kolli hills were documented. A questionnaire was prepared, with selected 17 ITAPs of tapioca for assessing the rationality of crop production and protection aspects of tapioca and was referred to 50 scientists, by rating them on a four point continuum ranging from 4 to 1.Having identified and selected the list of ITAPs with their rationality scores, further analysis was undertaken to test verify their extent of adoption and perceived effectiveness. The rational and effective ITAPs should be blended into the technology package for transfer of technology, so that the agricultural development will be sustainable.